Brand Portfolio Strategy for Mergers and Acquisitions - Simonova, Olga; Lhotáková, Markéta, 1971-; Král, Petr, 1979-; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2015)
This study represents an analysis of theoretical frameworks around brand integration strategies after mergers and acquisitions. The theoretical part of the paper is dedicated to the importance of brand equity, motives and advantages of brand acqui-sition and defines possible frameworks for brand integration strategies. A case study has been conducted on the application of the possible brand integration strategies based on an in-depth interview and thorough analysis of the outcomes of a specific acquisition in the domestic appliances industry
Vedoucí práce: Markéta Lhotáková
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2015
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2015
Způsob přístupu: Internet
Keywords: international management [obor dipl. práce]; diplomové práce; master's theses